2013
DOI: 10.1161/strokeaha.113.002589
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Aerobic Fitness Sustained Throughout the Adult Lifespan Is Associated With Improved Cerebral Hemodynamics

Abstract: Background and Purpose-Age-related impairments in cerebral blood flow and cerebrovascular reactivity to carbon dioxide (CVR CO2 ) are established risk factors for stroke that respond favorably to aerobic training. The present study examined to what extent cerebral hemodynamics are improved when training is sustained throughout the adult lifespan. Methods-Eighty-one healthy males were prospectively assigned to 1 of 4 groups based on their age (young, ≤30 years versus old, ≥60 years) and lifetime physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
206
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(232 citation statements)
references
References 16 publications
20
206
4
2
Order By: Relevance
“…Individuals who are taking antihypertensive medications or participating in regular exercise were excluded for their potential impact on cerebral and central hemodynamics. [12][13][14] This study was approved by the Institutional Review Board of the University of Texas Southwestern Medical Center and Texas Health Presbyterian Hospital Dallas, and was performed in accordance with the guidelines of the Declaration of Helsinki and Belmont Report. All subjects gave informed written consent before participation.…”
Section: Study Participantsmentioning
confidence: 99%
“…Individuals who are taking antihypertensive medications or participating in regular exercise were excluded for their potential impact on cerebral and central hemodynamics. [12][13][14] This study was approved by the Institutional Review Board of the University of Texas Southwestern Medical Center and Texas Health Presbyterian Hospital Dallas, and was performed in accordance with the guidelines of the Declaration of Helsinki and Belmont Report. All subjects gave informed written consent before participation.…”
Section: Study Participantsmentioning
confidence: 99%
“…Recent studies (4, 49) also reported a lack of an association between fitness and MCAv mean in young vs. older individuals. In contrast, life-long physical activity/training has shown an attenuated age-dependent decline in resting MCAv mean (2,3) and CBF (2,3,46). When the same relative exercise intensities were compared the trained study participants displayed a higher PaCO 2 in the control trial, and this was independent of age.…”
Section: Discussionmentioning
confidence: 87%
“…Whether fitness is a factor affecting CBF during exercise remains unclear. Moreover, aerobic fitness may affect hypercapnic cerebrovascular reactivity (4,32,49), although these findings are also contradictory as increased (3,32), unchanged (49) and decreased (46) hypercapnic reactivity has been reported in aerobically trained individuals. Again potential influencing factors for the widespread results could include differences in age and fitness levels across studies.…”
mentioning
confidence: 96%
See 2 more Smart Citations